An online programme to prepare teacher tutors: An experience involving a university-school partnership - Rinaldi, Renata Portela [UNESP]; Monteiro, Maria Iolanda; de Medeiros Rodrigues Reali, Aline Maria; Anunciato de Oliveira, Rosa Maria Moraes (Springer Nature, 2013)
The Universidade Federal de São Carlos (UFSCar) has become a partner with Open University of Brazil (UAB) to offer five undergraduate programmes at a distance, among which is K-4 Teacher Education (LPe-UAB/UFSCar). The overall goal of this online programme is to carry out actions, programmes, projects, and activities related to public policies elaborated so as to expand opportunities of access to quality, tuition-free higher education in Brazil.